Проблемні питання інноваційного розвитку підприємств-виробників молока в системі управління продовольчою безпекою в Україні - Чуб, Олег Анатолійович; Подсоха, Анна Сергіївна (Національний технічний університет "Харківський політехнічний інститут", 2025)
Виявлено основні фінансові та організаційні бар’єри, що істотно стримують інноваційний розвиток даних підприємств, серед яких домінують дефіцит власних інвестиційних ресурсів, складність доступу до кредитування, відсутність дієвих механізмів державної підтримки, а також недосконалість управлінських структур та дефіцит кваліфікованих кадрів. З’ясовано, що ці чинники безпосередньо впливають на зниження рівня технологічної модернізації молочного виробництва, що своєю чергою послаблює його здатність гарантувати продовольчу безпеку країни. Доведена необхідність удосконалення програм фінансової підтримки підприємств молочної галузі, розвитку коопераційних моделей та кластерних структур для забезпечення ефективного використання ресурсів і впровадження новітніх технологій. Також акцентовано увагу на стратегічній значущості інвестицій у людський капітал як передумови підвищення інноваційної спроможності підприємств даної галузі.

Several financial and organizational barriers were identified that significantly hinder the innovative development of these enterprises, among which the deficit of their own investment resources, the difficulty of access to credit, the lack of effective mechanisms of state support, as well as the imperfection of management structures and the shortage of qualified personnel dominate. It was found that these factors directly affect the decrease in the level of technological modernization of dairy production, which in turn weakens its ability to guarantee the country's food security. The importance of establishing effective interaction between producers, scientific institutions, and state bodies to activate the transfer of innovations and accelerate modernization processes is substantiated. The need to improve financial support programs for dairy enterprises, the development of cooperation models and cluster structures to ensure the effective use of resources, and the introduction of the latest technologies is proven. A list of measures for the post-war development of milk producers in Ukraine is formulated to create a powerful technological basis for their development, considering the impact on the parameters of food policy. Attention is also focused on the strategic importance of investments in human capital as a prerequisite for increasing the innovative capacity of enterprises in this industry.
Problems of innovative development of milk producing enterprises in the food safety management system in Ukraine
Keywords: інноваційний розвиток; продовольча безпека; аграрне підприємство; виробник молока; фінансування; економічні результати; людський капітал; innovative development; food security; agricultural enterprise; milk producer; financing; economic results; human capital